2022
DOI: 10.1002/acp.4025
|View full text |Cite
|
Sign up to set email alerts
|

Once (but not twice) upon a time: Narrative inoculation against conjunction errors indirectly reduces conspiracy beliefs and improves truth discernment

Abstract: Psychological inoculation has proven effective at reducing susceptibility to misinformation. We present a novel storytelling approach to inoculation against susceptibility to the conjunction fallacy (d meta-analysis = 0.82), a known cognitive predictor of conspiracy beliefs. In Study 1 (Pilot; N = 161), a narrative inoculation (vs. control) reduced susceptibility to conjunction errors, and in turn, conspiracy beliefs regarding government malfeasance. In Study 2 (main experiment; N = 141; pre-registered), two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Major misinformation themes included health (k=15) and climate change (k=7), the mean participant age distribution was 18 to 48 years, and most studies were conducted in the United States (k=28). A total of 31 studies reported misinformation credibility assessment [ 7 , 13 , 14 , 16 , 22 - 24 , 26 - 28 , 39 - 48 ], 26 reported real information credibility assessment [ 1 , 7 , 14 - 16 , 22 - 24 , 27 , 41 - 43 , 49 - 54 ], 12 reported credibility discernment [ 7 , 23 , 24 , 27 , 41 ], 12 reported misinformation sharing intention [ 7 , 13 , 23 , 40 , 45 , 50 ], 11 reported real information sharing intention [ 7 , 23 , 51 , 55 ], and 8 studies reported sharing discernment [ 7 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Major misinformation themes included health (k=15) and climate change (k=7), the mean participant age distribution was 18 to 48 years, and most studies were conducted in the United States (k=28). A total of 31 studies reported misinformation credibility assessment [ 7 , 13 , 14 , 16 , 22 - 24 , 26 - 28 , 39 - 48 ], 26 reported real information credibility assessment [ 1 , 7 , 14 - 16 , 22 - 24 , 27 , 41 - 43 , 49 - 54 ], 12 reported credibility discernment [ 7 , 23 , 24 , 27 , 41 ], 12 reported misinformation sharing intention [ 7 , 13 , 23 , 40 , 45 , 50 ], 11 reported real information sharing intention [ 7 , 23 , 51 , 55 ], and 8 studies reported sharing discernment [ 7 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Articles published by the same author in the same year are distinguished by a and b . Different studies in the same article are distinguished by an underscore and the numbers 1 to 6 [ 1 , 7 , 14 - 16 , 22 - 24 , 27 , 41 - 43 , 49 - 54 ]. SMD: standardized mean difference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This bias "occurs when the likelihood of two independent events occurring together is incorrectly assumed to be higher than the likelihood of the events occurring alone. " 58 That extremist influencers may be able to induce cognitive overload to thwart counter narratives is an area of study that is worthy of further exploration. While it is known that "established prejudices and ideological beliefs" along with a human tendency to "passively believe… information that follows existing preconceptions" results in people "accepting information uncritically" 59 less scholarship has focused on the permissive environments extremist influencers and their cascades cultivate.…”
Section: Expanding the Conventional Pcve Modelmentioning
confidence: 99%
“…Although the thought‐listing exercise was not effective on its own, the conjunction fallacy training did significantly reduce belief in conspiracy theories. Similarly, Biddlestone et al (2022) used a novel narrative inoculation message to immunize people against the conjunction fallacy beforehand. Across two studies, the authors found that the process of psychological inoculation reduced people's belief in conspiracy theories indirectly through the fact that people made far fewer conjunction errors.…”
Section: New Insights For Countering Belief In Conspiracy Theoriesmentioning
confidence: 99%